Alternative Splicing of Cdh23 Exon 68 Is Regulated by RBM24, RBM38, and PTBP1. (25th July 2020) - Li, Nana; Du, Haibo; Ren, Rui; Wang, Yanfei; Xu, Zhigang
Abstract : Alternative splicing plays a pivotal role in modulating the function of eukaryotic proteins. In the inner ear, many genes undergo alternative splicing, and errors in this process lead to hearing loss. Cadherin 23 (CDH23) forms part of the so-called tip links, which are indispensable for mechanoelectrical transduction (MET) in the hair cells. Cdh23 gene contains 69 exons, and exon 68 is subjected to alternative splicing. Exon 68 of the Cdh23 gene is spliced into its mRNA only in a few cell types including hair cells. The mechanism responsible for the alternative splicing of Cdh23 exon 68 remains elusive. In the present work, we performed a cell-based screening to look for splicing factors that regulate the splicing of Cdh23 exon 68. RBM24 and RBM38 were identified to enhance the inclusion of Cdh23 exon 68. The splicing of Cdh23 exon 68 is affected in Rbm24 knockdown or knockout cells. Moreover, we also found that PTBP1 inhibits the inclusion of Cdh23 exon 68. Taken together, we show here that alternative splicing of Cdh23 exon 68 is regulated by RBM24, RBM38, and PTBP1.